Amyad's hernia while reparing the bilateral inguinal hernia - Arif Aslaner; Tuğrul Çakır; Umut Rıza Gündüz; Burhan Mayir; Nurullah Bülbüller (American Journal of Experimental and Clinical Research, 2015)
Amyand's hernia is the term used for inguinal hernia containing appendix. It is a rare condition and found in 1% of inguinal hernia repairs. Here we report a case of Amyand's hernia in a 61 years old male who was diagnosed with bilateral inguinal hernia. He underwent surgery and bilateral inguinal hernia repair with prosthetic meshes and without appendectomy. The patient was discharged uneventfully.